Stability analysis of ‘roof-coal pillar’ structure in longwall multi-section mining of steeply dipping coal seam - Yongping Wu; Yepeng Tang; Panshi Xie; Bosheng Hu; Ding Lang; Hongwei Wang (Geomatics, Natural Hazards & Risk)
To solve the problem of stability control of coal pillar in steeply dipping coal seam (SDCS), based on the characteristics of surrounding rock structure and stress environment of the coal pillar, a special bearing structure of ‘roof-coal pillar’ combination is proposed through theoretical analysis. The mechanical model of inclined ‘roof-coal pillar’ structure is established, and the stress and strength characteristics of each element in the structure are deduced. Combining numerical calculations (PFC2D-FLAC2D coupling model) and physical similarity simulation, the stress evolution characteristics and failure mechanism of the ‘roof-coal pillar’ structure under the influence of mining were revealed. The results show that the coal pillar of SDCS is easy to form a ‘roof-coal pillar’ combined bearing structure with the roof strata. Under the influence of mining, the stress distribution and deformation evolution within the ‘roof-coal pillar’ structure show strong non-uniform and asymmetric characteristics. Among them, the stress distribution shows an ‘ellipse’ shape which is offset to the upper section, and the main deformation zone of the structure is a diagonal deformation distribution zone that runs through the coal and rock in the same direction as the stress offset. The failure of the ‘roof-coal pillar’ structural firstly occurs in the coal area near the coal-rock interface on the side of the lower section, and finally forms a diagonal failure crack running through the coal and roof, which is manifested as a diagonal shear failure mode. The findings can provide a theoretical basis for the stability control of coal pillars in multi-section mining of SDCSs and improve the safety production technology level of the working face.